PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN PENDEKATAN KONSTRUKTIVIS DI KELAS IV SD - Handoko, Bagus Tri; Miaz, Yalvema; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
Purpose of this study was to describe the use of contructivist approach to improve student learning outcomes in learning science in grade four  of SD Negeri 06 Kampung Pansur Tarusan Pesisir Selatan  in the fourth grade students numbering twenty people. This research uses qualitative and quantitative approaches. This type of research is a classroom action research (PTK). The results of the first cycle students learning 81,25 increased to 91  in  the second cycle. Therefore, countructivist approach can improve student learning outcomes in social studies in the fourth grade of SD Negeri 08Gadut Kecamatan Tilatang Kamang.